The Titanic an interactive history adventure - Temple, Bob (Mankato, Minn. Capstone Press, 2008)
"Describes the events surrounding the sinking of the ship Titanic in 1912. The reader's choices reveal the historical details from the perspective of a first-class passenger, a third-class passenger, and a crewmember"--Provided by publisher.
Includes bibliographical references (p. 11) and index.
3-4.
3-7.
A Junior Library Guild selection
Keywords: Titanic (Steamship) -- Juvenile literature; Shipwrecks -- North Atlantic Ocean -- Juvenile literature